Rupture and Resistance: Nivaldo Ornelas’ Contributions to the Music of Milton Nascimento in the Recording of the Song “Hoje É Dia de El Rey” - Fabris, Bernardo (Intermédialités / Intermediality, 2021)
Brazilian musicians Milton Nascimento and Nivaldo Ornelas began working together in the 1960s in Belo Horizonte. This was a decade of great transformations for global geopolitics as well as Brazilian society, which was undergoing a rapid growth of urban centers coupled with rural outmigration. During this period, two fields of cultural production emerged in popular music that would become paradigmatic for Brazilian music, namely, música popular brasileira, or MPB, and Brazilian Instrumental Music. This article aims to describe the intersections of these two fields of artistic production by examining the contributions of saxophonist Nivaldo Ornelas to the recordings of Nascimento’s song “Hoje É Dia de El Rey,” understood as manifestations of resistance and resilience of subaltern voices as a decolonial alternative to hegemonic projects—whether within aesthetic, political, racial, or economic scenarios.